The Translation Strategy of Larson Applied in The Translation of Similes in ‘A Walk to Remember’ Novel by Nicholas Sparks - Bunadi, Stefanie Keren (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
In translating similes, the main challenge is to ensure that the comparison from the source language conveys the intended meaning in the translated version, allowing readers to fully understand the original meaning. This research aims to find out the translation strategy in translating the simile found in “A Walk to Remember” novel by Nicholas Sparks from English as the source language and Indonesian with the title “Kan Kukenang Selalu” as the target language. This research used a qualitative method in collecting and identifying the data. There are three strategies in translating figurative languages using Larson’s strategies (1998), which consist of; the sense of the word may be translated non-figuratively, retain the word in the original but to add the sense of the word, and substitute a figurative expression of the target language for the figurative expression of the source language.